Birth order and alcohol-related mortality by ethnic origin and national context: Within-family comparisons for Finland and Sweden. (1st September 2021) - Saarela, Jan; Kolk, Martin
Highlights: First study on the association between birth order and alcohol-related mortality. Later-borns are more likely than first-borns to die from an alcohol-related cause. The pattern pertains only to ethnic Finns in Finland, and particularly men. No positive correlation in Sweden or in other ethnic groups. The association is dependent on ethnic origin and national context. Abstract: Background: Previous studies have found that birth order is an important predictor of later life health, including hospitalisation for alcohol use. We examine the relationship between birth order and alcohol-related mortality in two national contexts, within native families who differ on ethnic origin. Methods: We study the association between birth order and alcohol-related mortality after age 17, using Finnish register data for cohorts born 1953−1999 and Swedish register data for cohorts born 1940−1999. We apply Cox proportional hazard models and use sibling fixed effects that eliminate confounding by factors shared by siblings. We separate full-sibling groups by ethnic origin, which for Finland means mother's and father's Finnish or Swedish ethnolinguistic affiliation. For Sweden, we distinguish native-born according to whether one or both parents were born in Sweden or Finland. Results: We find a positive correlation between birth order and alcohol-related mortality, but only for ethnic Finns in Finland and primarily men. Within these sibling groups, second-borns have an alcohol-related mortality risk that is 9% higher than that of first-borns, third-borns 19 % higher, fourth-borns 22 % higher, and fifth- or higher-borns 47 % higher. No such birth order associations can be found for any of the other ethnic groups analysed in Finland or Sweden. Conclusions: Our findings suggest that cultural-related behaviours typical for ethnic groups, and the national context in which they are studied, are relevant for whether any association between birth order and alcohol-related mortality can be observed. Differences in the social interplay within the family may be an important factor.